Relationship between maternal exposure to heavy metal titanium and offspring congenital heart defects in Lanzhou, China: A nested case-control study - Sun, Jianhao; Mao, Baohong; Wu, Zhenzhen; Jiao, Xinjuan; Wang, Yanxia; Lu, Yongli; Ma, Xuejing; Liu, Xiaohui; Xu, Xiaoying; Cui, Hongmei; Lin, Xiaojuan; Yi, Bin; et al. (Frontiers in Public Health, 2022)
Background Previous studies have found that exposure to heavy metals increased the incidence of congenital heart defects (CHDs). However, there is a paucity of information about the connection between exposure to titanium and CHDs. This study sought to examine the relationship between prenatal titanium exposure and the risk of CHDs in offspring. Methods We looked back on a birth cohort study that was carried out in our hospital between 2010 and 2012. The associations between titanium exposure and the risk of CHDs were analyzed by using logistic regression analysis to investigate titanium concentrations in maternal whole blood and fetal umbilical cord blood. Results A total of 97 case groups and 194 control groups were included for a nested case-control study. The [P50 (P25, P75)] of titanium were 371.91 (188.85, 659.15) μg/L and 370.43 (264.86, 459.76) μg/L in serum titanium levels in pregnant women and in umbilical cord serum titanium content in the CHDs group, respectively. There was a moderate positive correlation between the concentration of titanium in pregnant women's blood and that in umbilical cord blood. A higher concentrations of maternal blood titanium level was associated with a greater risk of CHDs (OR 2.706, 95% CI 1.547–4.734), the multiple CHDs (OR 2.382, 95% CI 1.219–4.655), atrial septal defects (OR 2.367, 95% CI 1.215–4.609), and patent ductus arteriosus (OR 2.412, 95% CI 1.336–4.357). Dramatically higher concentrations of umbilical cord blood levels had an increased risk of CHDs and different heart defects. Conclusion Titanium can cross the placental barrier and the occurrence of CHDs may be related to titanium exposure.